Implementasi Konsep Smart City Melalui Pengembangan Wilayah Kabupaten Simeulue - Idal Bahri; Yunida Pangastuti; Mohd. Isa T. Ibrahim (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2021)
Regional development can give birth to new cities that can be implemented in the smart city concept which is a trend in Indonesia. This is a logical consequence of regional expansion based on the demands of local communities, it should be addressed wisely by directing and implementing a comprehensive, strategic and integrated planning concept that does not only rely on local strengths, but also considers the strengths of the surrounding area so that it is hoped that linkages will be created. functional between regions. Structuring a New City as a Smart City means optimizing land functions that aim to balance and create integration between urban areas which after the activity can guarantee and support environmental sustainability as a whole, improve the economy (improvement of economic conditions) and socially. welfare (social welfare). ) society in the future